Prototyping with Microsoft .NET Gadgeteer - Villar, Nicolas; Scott, James; Hodges, Steve (Proceedings of the Fifth International Conference on Tangible, Embedded, and Embodied Interaction, 2011)
Microsoft .NET Gadgeteer is a new prototyping platform that makes it easier to construct, program and shape new kinds of computing objects. It is comprised of modular hardware, software libraries and 3D CAD support. Together, these elements support the key activities involved both in the rapid prototyping and the small-scale production of custom embedded, interactive and connected devices. We propose to organize and run a studio at TEI 2010 where participants are introduced to the platform and its capabilities. Participants will work in groups, assembling electronic modules, writing software and designing a case or enclosure for their device. The end-result will be that each group develops a fully functional device, which can be exhibited at the TEI demo session.